(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Video Clips as a medium of communication to express works of art and culture are widely used by the younger generation. Some research shows the younger generation uses more attention to environmental damage through video clips. Mara Karma a music band indie through with “Stories of the past” protested against the destruction of the developmental environment technology and Industrialization. Through semiotic analysis, this study aims to determine the meaning to be conveyed and the resistance to be addressed to whom. With the semiotics of Charles Sanders Peirce through the triatidic meaning, 10 scenes were analyzed to show strong diction Modernization cause environmental damage in the region urban. Anger and demands for the product of Modernity’s diction as a form of resistance have run out of ways. This study concludes that meaning.